Wind energy resource assessment in gap regions using MM5 numerical weather prediction model - Dorilag, Raphael B. (2013)
Wind energy resource assessment is conducted to determine the feasibility of putting up a wind power project at a given site. Current wind resource assessment methods have constraints such as relatively operating cost, coarse resolution, data representativeness and availability. In this study, the PSU/NCAR 5th Generation Mesoscale Model (MM5) numerical weather prediction model with up to 1.33-km grid resolution was used to characterize the wind resource in island gaps in the central Philippines. The MM5 model was calibrated with 10-m wind speed measurement in Barotac Nuevo, Iloilo and Buenavista, Guimaras afore the different grid resolution and planetary boundary layer schemes. A 1-year MM5 simulation was the implemented to generate a wind resource map and identify potential sites. The total energy production and capacity factor for these sites were calculated given the power curve of selected wind turbines. Results showed that MM5 was able to simulate topography effects such as wind acceleration on mountain ridges and in island gaps. The average wind speed and direction map showed that gap wind effects are found in Luzon-Mindoro, Mindoro-Panay and in Panay-Negros wind corridor. The MM5 simulation in Barotac Nuevo had a better fir with observation with an RMSE of 1.87 m/s and a correlation coefficient of 0.53 for hourly-average wind speed. Potential sites with WPD greater than300 W/m² were identified in islands and coastal locations near the gap wind region from the MM5 generated wind speed, wind power density, wind rose plot and monthly-averaged wind speed. The selection of the best wind resource sites does not depend only on the average wind speed and wind power density but also on the suitability of the proposed wind turbine design to the wind speed distribution.
Thesis (M.S. Energy Engineering)--University of the Philippines, Diliman.
Keywords: Wind power -- Research